2023
DOI: 10.1021/acs.jafc.2c04211
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Activation Is Not a Common Feature of Angiotensin-Converting Enzyme Inhibitory Peptides

Abstract: Angiotensin-converting enzyme (ACE) catalyzes the formation of angiotensin II (Ang II), a vasoconstrictor, whereas its homologue ACE2 degrades Ang II into angiotensin (1–7) (Ang (1–7)), a vasodilator. Given the similarities in structure and their interconnected roles in the regulation of cardiovascular system, this study aims to investigate if ACE-inhibitory (ACEi) peptides can also activate ACE2. About 200 potent ACEi peptides were subjected to molecular docking, 20 peptides were selected for cell and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In this study, SNHANQLDFHP could significantly increase the activity of ACE2 in EA.hy926 cells at the concentrations of 100−500 μg/mL, and PVQVLASAYR displayed a similar effect at the concentration of 500 μg/mL (p < 0.05) as depicted in Figure 6D. However, activating ACE2 activity is not a common feature of ACE inhibitory peptides as confirmed in the study by Wang et al, 48 which found 8 (IQP, YQY, MRW, RIY, IKP, FFY, AKK, and IEF) out of 20 selected ACE inhibitory peptides had no effects on ACE2 levels. Although peptides with ACE inhibition activity had been previously identified from pumpkin seed proteins, 17,19,20 SNHANQLDFHP and PVQVLASAYR obtained in this study were the first PSM-derived peptides reported to have both ACE inhibition and ACE2 upregulation activities in endothelial cells.…”
Section: ■ Discussionsupporting
confidence: 82%
“…In this study, SNHANQLDFHP could significantly increase the activity of ACE2 in EA.hy926 cells at the concentrations of 100−500 μg/mL, and PVQVLASAYR displayed a similar effect at the concentration of 500 μg/mL (p < 0.05) as depicted in Figure 6D. However, activating ACE2 activity is not a common feature of ACE inhibitory peptides as confirmed in the study by Wang et al, 48 which found 8 (IQP, YQY, MRW, RIY, IKP, FFY, AKK, and IEF) out of 20 selected ACE inhibitory peptides had no effects on ACE2 levels. Although peptides with ACE inhibition activity had been previously identified from pumpkin seed proteins, 17,19,20 SNHANQLDFHP and PVQVLASAYR obtained in this study were the first PSM-derived peptides reported to have both ACE inhibition and ACE2 upregulation activities in endothelial cells.…”
Section: ■ Discussionsupporting
confidence: 82%
“…Another example is MRW, derived from Rubisco, which effectively lowers the blood pressure in SHRs. Unlike IRW, MRW achieves its blood pressure-lowering activity through prostaglandin D2-dependent vasorelaxation rather than ACE2 upregulation. , These findings collectively suggest the novelty of peptide IRW.…”
Section: Discussionmentioning
confidence: 82%
“…The aorta is a potential target of ACE2 upregulatory peptides, including IRW. , Therefore, the aortic ACE2 levels in SHRs treated with IR and tryptophan were assessed. As shown in Figure , tryptophan treatment significantly increased ACE2 protein levels, with a p value of 0.011.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations